THE INTERPLAY OF GEOGRAPHY AND HISTORY: SHAPING THE COURSE OF HUMAN CIVILIZATION - Anorboyev , Xayrulla; Eraliyeva , Mehrinisso (Educational Research in Universal Sciences, 2023)
Geography and history are intertwined disciplines that shape the course of human civilization. The physical features of our planet have not only provided the backdrop for historical events but have also played a pivotal role in influencing the development and interactions of societies. This essay explores the dynamic relationship between geography and history, delving into how geographical factors have shaped historical events and, in turn, how human activities have left a lasting imprint on the landscape.